Effects of trophic poisoning with methylmercury on the appetitive elements of the agonistic sequence in fighting-fish (Betta Splendens) - Gouveia Jr., Amauri [UNESP]; De Oliveira, Caio Maximino [UNESP]; Romão, Cynthia Ferreira [UNESP]; De Brito, Thiago Marques [UNESP]; Ventura, Dora Fix (Cambridge University Press (CUP), 2007)
The aggressive display in Betta splendens is particularly prominent, and vital to its adaptation to the environment. Methylmercury is an organic variation of Hg that presents particularly pronounced neuro-behavioral effects. The present experiments aim to test the effect of acute and chronic poisoning with methylmercury on the display in Bettas. The animals were poisoned by trophic means in both experiments (16 ug/kg in acute poisoning; 16 ug/kg/day for chronic poisoning), and tested in agonistic pairs. The total frequency of the display was recorded, analyzing the topography of the agonistic response. The methylmercury seems to present a dose- and detoxification-dependent effect on these responses, with a more pronounced effect on motivity in acute poisoning and on emotionality in the chronic poisoning. It is possible that this effect could be mediated by alteration in the mono-amino-oxidase systems. Copyright 2007 by The Spanish Journal of Psychology.
Keywords: Aggression; Betta splendens; Emotional behavior; Methylmercury